Constitutional control and social solidarity economy: legal architecture of Colombian cooperative law (1991–2010) - Vargas Machado, Camilo Andrés; Armenta Calderón, Julie Carolina (Cooperativismo & Desarrollo, 2025)
This review article analyzes how the Colombian Constitutional Court interprets and legally strengthens the social solidarity economy in tension with the market. It seeks to demonstrate how, since 1991, the Court has interpreted and defined the solidarity economy and cooperative law from a guarantee-based perspective. The constitutional scope of the social solidarity economy is discussed, where the central dispute revolves around its tension with state intervention. To this end, a qualitative design using an inductive method and an interpretive paradigm was adopted, applying a hermeneutic approach, using a documentary and document review technique. A documentary sample of 239 constitutional actions for protection and constitutional control was then selected. 13 constitutional control rulings were then selected, using one analytical category and three theoretical categories. This allowed us to reveal constitutional norms, legislative gaps, and jurisprudential convergences that configure a plural, dynamic, and guarantee-based model. Concluding that the Court has consolidated a guarantee-based doctrine by harmonizing solidarity-based self-management and state control, and that cooperative law can guide the strengthening of cooperativism and the social solidarity economy. Cooperative law constitutes the regulatory framework; cooperativism, its ideological expression; and the solidarity economy, the unifying socioeconomic system.